Modelagem tridimensional de problemas inversos em condução de calor: aplicação em problemas de usinagem - Lima, Frederico Romagnoli Silveira (2001)
This work proposes a methodology to obtain the transient cutting tool temperature. The physical phenomenon is treated by a three-dimensional analysis. The inverse heat conduction technique is proposed to estimate the generated heat flux on the rake face of the tool. This technique is based on conjugate gradient method with adjoint equation. The machining process is instrumented with thermocouples at the bottom face of the tool, opposite to its main rake face. The signals are automatically received and processed using a data acquisition system and a PC-Pentium. The direct solution is numerically solved using finite volumes method with the heat flux estimated. The experimental data are processed using a computational algorithm developed specifically for inverse heat flux estimation in machining processes. Experimental temperatures are obtained during several cutting tests using cemented carbide and ceramic tools. The influence of the cutting parameters on the temperature distribution is verified. An error analysis of the results is also presented.